Kinetic Consideration of Clinker Formation in Portland Cement Production Using Demolition Rubbles (Concrete,mortar and plaster) Part I : Burning Ability of Raw Mixes - Sumardi P; I. B. Agra; I. M. Bendiyasa; Wahyudi B. S. (ASEAN Journal of Chemical Engineering, 2005)
Wahyudi B.S.Wahyudi B.S.In general, the main raw materials in Portland cement production are limestone, clay, and corrective materials such as iron sand and silica sand. These raw material come from natural deposits, which are very hard to find in some countries. In this research, Portland cement was made by utilizing the demolition rubble of office and housing buildings. The rubble consists of concrete wastes (mixtures of hydrated Portland cement minerals and some aggregates) and some building bricks as well as mortar/plaster of Portland cement. To meet the cement modulus, which is generally used in Portland cement industries, corrective materials such as limestone (source of CaO) and disposed building bricks are used. The term burning ability is used for Portland cement to measure the CaO free content in the cement clinker produced from specified raw material mixes at a specific operating 'condition of clinkering. The cement modulus used is Ume Saturation Factor (LSF) and Silica Modulus (SM). The minimum Cao free content was found by using LSF: 0.86, SM: 2.14, and clinkering temperature 14000C for 30 minutes. The cement modulus was made from concrete waste, limestone, and disposed red brick with a weight ratio of 1: 3.489: 0.677. Keywords: Burning ability,demolition rubble of buildings, Portland cement, and raw mixes.